153k views
5 votes
Which shows the correct substitution of the values a, b, and c from the equation 0 = – 3x2 – 2x + 6 into the quadratic formula? Quadratic formula: x =

2 Answers

5 votes

Answer:


x=(-(-2)\pm √((-2)^2-4(-3)(6)))/(2(-3))

Explanation:

The given quadratic equation is


-3x^2-2x+6=0 .... (1)

If a quadratic equation is defined as


ax^2+bx+c=0 .... (2)

then the quadratic formula is


x=(-b\pm √(b^2-4ac))/(2a)

On comparing (1) and (2), we get


a=-3,b=-2,c=6

Substitute
a=-3,b=-2,c=6 in the above formula.


x=(-(-2)\pm √((-2)^2-4(-3)(6)))/(2(-3))

Therefore, the correct substitution of the values a, b, and c in the quadratic formula is
x=(-(-2)\pm √((-2)^2-4(-3)(6)))/(2(-3)).

User AKZap
by
5.3k points
6 votes

Answer:

The answer in the procedure

Explanation:

we know that

The formula to solve a quadratic equation of the form
ax^(2) +bx+c=0 is equal to


x=\frac{-b(+/-)\sqrt{b^(2)-4ac}} {2a}

in this problem we have


0=-3x^(2) -2x+6

so


a=-3\\b=-2\\c=6

substitute in the formula


x=\frac{-(-2)(+/-)\sqrt{-2^(2)-4(-3)(6)}} {2(-3)}


x=\frac{2(+/-)√(74)} {-6}


x=\frac{-2-√(74)} {6}


x=\frac{-2+√(74)} {6}

User Chris Brendel
by
4.8k points